Toxic epidermal necrolysis with thrombocytopenia induced by intravenous immunoglobulin: a case report and mini review - Yoshihiro Nishita; Masatoshi Taga; Nozomi Arakawa; Tomoki Ishida; Sawako Ochiai; Hiroto Ono; Fumiaki Taga; Togen Masauji (Journal of Pharmaceutical Health Care and Sciences)
Abstract Background Toxic epidermal necrolysis (TEN), a severe cutaneous hypersensitivity reaction induced particularly by drugs, is diagnosed when there is a fever of ≥ 38 °C, mucocutaneous symptoms, a rash with multiple erythema, and skin peeling of ≥ 30% of the body surface area. The mortality rate of TEN is high, and thrombocytopenia during treatment can lead to severe outcomes. Intravenous immunoglobulin (IVIg) is used when steroids are ineffective in TEN and may improve mortality; however, thrombocytopenia is a rare adverse event associated with IVIg use. We report the case of thrombocytopenia during IVIg therapy for TEN. We also reviewed previous reports to learn more about the clinical course and mechanism of IVIg-induced thrombocytopenia. Case presentation An 83-year-old man with end-stage renal failure on hemodialysis was diagnosed with TEN. After an inadequate response to pulse methylprednisolone therapy, IVIg (400 mg/kg/day) was administered for 5 days. He developed thrombocytopenia after IVIg administration, leading to the diagnosis of thrombocytopenia due to IVIg after excluding other diseases. The platelet count began to increase approximately 10 days after IVIg administration. Conclusions When IVIg is administered for TEN, the risk of thrombocytopenia should be recognized and the platelet count should be carefully monitored.